Values of prognostic nutritional index for predicting Kawasaki disease: a systematic review and meta-analysis - Zhong, Xiaoling; Xie, Yu; Wang, Hui; Chen, Guihua; Yang, Taoyi; Xie, Jiang (Frontiers in Nutrition, 2024)
Objective: This systematic review and meta-analysis aimed to evaluate the relationship between the prognostic nutritional index (PNI) and intravenous immunoglobulin (IVIG) resistance and coronary artery lesion (CAL) in Kawasaki disease (KD).The relevant literature was searched on PubMed, Embase, Cochrane Library, Web of Science, and Google Scholar up to August 05, 2023. A pooled sensitivity, specificity, positive likelihood ratio (PLR), negative likelihood ratio (NLR), diagnostic odds ratio (DOR) and area under curve (AUC) were calculated to assess the predicted values of PNI in KD patients with IVIG resistance and CAL.Results: A total of 8 articles containing 10 studies involving 7047 participants were included. The pooled results revealed a pooled sensitivity of 0.44 (0.25-0.65), a pooled specificity of 0.87 (0.73-0.94), a pooled PLR of 3.4 (2.0-5.9), a pooled NLR of 0.65 (0.48-0.87), a pooled DOR of 5.26 (2.76-10.02), and a pooled AUC of 0.75 (0.71-0.78) in the diagnosis of KD with CAL. The pooled results suggested that a pooled sensitivity was 0.69(0.60-0.77), specificity was 0.76(0.69-0.82), PLR was 2.9(2.1-4.1), NLR was 0.40(0.29-0.56), DOR was 7.27 (3.89-13.59), and AUC was 0.79(0.75-0.82) in the diagnosis of KD with IVIG resistance. The combined results revealed the pooled sensitivity was 0.63(0.58-0.67), specificity was 0.82(0.80-0.83), PLR was 3.09(1.06-8.98), NLR was 0.38(0.07-2.02), ) in differentiating KD from febrile patients. These findings demonstrated low sensitivity and relatively high specificity of PNI for KD, KD-CAL, and IVIG-resistant KD.In conclusion, this study was the first systematic review and metaanalysis of the diagnostic value of PNI in KD with IVIG resistance and CAL. The results suggested that PNI could be used as biomarkers for distinguish KD, KD with CAL, and KD with IVIG resistance.